Application of supramolecular solvent based on the surface-active ionic liquid in dispersive liquid–liquid microextraction of triazine herbicides in tea samples. (15th January 2023) - Li, Jilong; Wu, Fengze; Zhang, Yupu; Feng, Ji; Wang, Xiujuan; Yang, Yi; Wang, Zhibing; Zhang, Hanqi
Graphical abstract: Highlights: A novel SUPRAS was prepared for the first time using [BMIM]PF6 and THF. The SUPRAS-DLLME was developed for the extraction of triazine herbicides in tea samples. The prepared SUPRAS had good dispersion, low viscosity and high density. The microstructure of SUPRAS was analyzed by the calculation of packing factor. The SUPRAS were characterized by phase diagram, TEM, SEM, TGA, densimeter and viscometer. Abstract: In this study, a novel supramolecular solvent based on surface-active ionic liquid was prepared and used as an extraction solvent for dispersive liquid–liquid microextraction of four triazine herbicides in tea samples. The formation mechanism, microstructure and physicochemical properties of supramolecular solvent were studied. Some parameters, including the molar ratio of surface-active ionic liquid to tetrahydrofuran, volume of supramolecular solvent, vortex time, pH of sample solution, type and amount of salt, were investigated and optimized. The good linearities (r > 0.9990) for the analytes were obtained. The limits of detection and quantification for triazine herbicides were in the range of 1.7–2.1 μg kg −1 and 5.6–7.1 μg kg −1, respectively. The spiked recoveries were 80.0–119.9 %. The supramolecular solvent prepared in this study has the advantages of simple preparation process, low viscosity and good dispersibility. It can be used for the extraction and enrichment of trace triazine herbicides in tea samples.